Os megaeventos na produção do espaço urbano: análise da cidade do Rio de Janeiro (Brasil) - Viana, Lúcio Hanai Valeriano (2018)
This work analyzes the social and economic effects in cities that promoted deep urban changes to host mega events of global acknowledgement, especially in the City of Rio de Janeiro (Brazil). For this, the option was to conduct in-depth interviews with the technicians and experts directly and indirectly involved in the urban transformations which occurred in Barcelona (Spain) for having hosted the 1992 Olympic Games; in Lisbon, for the 1998 Lisbon World Exposition (Expo’98) and in Rio de Janeiro due to its recent experience in hosting the 2016 Olympic Games. The City of Rio de Janeiro, object of this study, was analyzed notedly regarding its political agenda, here considered essential for understanding the goals to be attained by the urban changes demanded for hosting the 2016 Olympic Games. Seeking to meet the aims of analyzing the political and ideological contents surrounding the mega events, this research focuses on the analysis of the relations of the power and interests circumscribing the application and election of the city. In the same perspective, aiming to identify the influence of the IOC in the management of urban public policies associated to mega events, the option was to analyze documentary sources (Report of the 2016 IOC, Olympic Charter) aiming to investigate the quality of its demands, counterparts and recommendations. For being a multidisciplinary theme, the theoretical framework permeates different knowledge areas. The theoretical approaches are concentrated on the urban sociology field, on public policies and on the neoclassical economics theory. From the public administration viewpoint, a great interest for real estate valorization could be verified as a way of regaining the investments made for carrying out mega events. This kind of management demonstrated the trend of spatial concentration of income, causing an aggravation in the city social inequalities. A strong influence of foreign urban models was observed, notedly from the Barcelona Model, characterized by the appropriation of capital gains on land and for transforming mixed-use public spaces into areas restricted to the wealthier social classes. The strategies for promoting mega events were verified to follow a standard dynamic which conditions the design of public policies of urban intervention to the “cost-benefit” logic (solely considering the quantitatively measurable aspects) to the detriment of social interests. The strategies for carrying out mega events were revealed to be markedly turned to the interests of the real estate market supported on managerial practices widely represented by neoliberalism